RNA meets disease in paradise - Winter, Julia; Roth, Anna; Diederichs, Sven (RNA biology, 2011)
Getting off the train in Jena-Paradies, 60 participants joined for the 12th Young Scientist Meeting of the German Society for Cell Biology (DGZ) entitled “RNA & Disease”. Excellent speakers from around the world, graduate students, postdocs and young group leaders enjoyed a meeting in a familiar atmosphere to exchange inspiring new data and vibrant scientific discussions about the fascinating history and exciting future of non-coding RNA research including microRNA, piRNA and long non-coding RNA as well as their function in cancer, diabetes and neurodegenerative diseases.
Gesehen am 07.11.2022